Relations Between Church and State in the New Peruvian Constitution - Interdonato, Francisco (1981)
The objective of this paper is to analyze the new relations between the Church and the Peruvian State because of the changes introduced by the 1979 Political Constitution of Peru. For this purpose, the proposal of the Doctrine of Vatican II on the relations between the Church and the State is examined, which will allow us to highlight the aspects that the Church and the States are renouncing in their interactions. The new aspects introduced by the 1979 Constitution are also examined. In this way, it is concluded that the doctrine of Vatican II is not followed in relations with the State, and that the 1979 Constitution introduces changes with respect to its predecessor, the Political Constitution of the Republic of 1933, which affect this relationship with the Church.